Racial and Ethnic Diversity in the Nursing Workforce: A Focus on Maternity Care. (August 2021) - Kozhimannil, Katy B.; Almanza, Jennifer; Hardeman, Rachel; Karbeah, J'Mag
Racial and ethnic inequities in health are a national crisis requiring engagement across a range of factors, including the health care workforce. Racial inequities in maternal and infant health are an increasing focus of attention in the wake of rising rates of maternal morbidity and mortality in the United States. Efforts to achieve racial equity in childbirth should include attention to the nurses who provide care before and during pregnancy, at childbirth, and postpartum.